Artificial cultivation of true morels: current state, issues and perspectives. (17th February 2018) - Liu, Qizheng; Ma, Husheng; Zhang, Ya; Dong, Caihong
Abstract: Morels ( Morchella, Ascomycota), which are some of the most highly prized edible and medicinal mushrooms, are of great economic and scientific value. Morel cultivation has been a research focus worldwide for more than 100 years, and the outdoor cultivation of morels has succeeded and expanded to a large scale in China in recent years. In this study, we review the progress in recent research regarding the life cycle and reproductive systems in the genus Morchella and the current state of outdoor cultivation. Sclerotia formation and conidia production are two important phases during the life cycle. The morel species cultivated commercially in America is M. rufobrunnea based on molecular phylogenetic analysis. The species currently cultivated in China are black morels, including M. importuna, M. sextalata and M. eximia . The field cultivation of morels expanded in the majority of the provinces in China with a yield of fresh morels of 0–7620 kg per ha. The key techniques include spawn production, land preparation and spawning, the addition of exogenous nutrition, fruiting management and harvesting. The application of exogenous nutrition is the most important breakthrough in the field of morel cultivation, but the mechanism remains unclear. It was estimated that the total amount of field cultivated fresh morels was ∼500 t in 2015–2016. We also discuss the potential issues remaining in the current literature and suggest directions for future studies.